66. Appropriate Distance Education Media in the Philippines and Mongolia - McDonald, Brenda (International Review of Research in Open and Distributed Learning, 2009)
Recent educational projects in the Philippines and Mongolia have revealed effective educational delivery methods as well as necessary changes to ensure DE access for as many learners as possible. A project initiated by Canada’s International Development Research Centre (IDRC) has stressed the value of DE delivery through cellular phone technology. As the cell phone becomes increasingly available in Mongolia and the Philippines, its use to deliver education promises to compensate for the relative lack of Internet access in these countries. The IDRC project illustrates how appropriate distance education methods in Asian countries will assist in economic and social development.